'Delicate and durable': An analysis of women's leadership and media practices in Vietnam. (1st March 2019) - Vu, Hong Tien; Barnett, Barbara; Duong, Hue Trong; Lee, Tien Tsung
The qualities of a good leader are frequently aligned with traditional gender norms: men are viewed as aggressive and competitive and are considered 'natural' leaders, while women are viewed as submissive and nurturing – qualities seen as antithetical to good leadership. The news media help shape public understanding of leadership through reporting, and to understand better the relationship between gender norms and leadership, this qualitative study examined journalists' perspectives on leadership in Vietnam, a country where women have played a role in building the country's financial stability but not necessarily benefitted from the country's economic progress. In-depth interviews were conducted with sixteen Vietnamese journalists (eight women and eight men) to explore their perspectives on women's roles as leaders in their home countries. Researchers learned that journalists have internalized traditional gender scripts. They acknowledge that women can be good leaders, but they question whether women should devote time and energy to work that takes them away from their families. Journalists say that, irrespective of whether women take on leadership roles, they must put family first; however, men are not held to the same standard. Research suggests that journalists see gender roles as fixed and men as the most suited for leadership roles.